Students’ Learning Difficulties in Blended Learning: A Case Study - Renica, Elvira Chrisdia; Irafahmi, Diana Tien (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2023)
Blended learning is a flexible learning environment that could enhance learning. However, its implementation has not been entirely successful, as many students still face difficulties in learning and adapting to this learning environment. This research aims to understand why students experience learning difficulties in blended learning. The research approach used is qualitative research with a case study design. The results of the study show that the learning difficulties experienced by accounting students in blended learning environment are caused by low self-regulated learning, inadequate family support, poor internet connectivity, lack of immediate feedback, communication barriers, and students dissatisfaction with online learning session.